2010
DOI: 10.1021/ja106631r
|View full text |Cite
|
Sign up to set email alerts
|

A Viable Anionic N-Heterocyclic Dicarbene

Abstract: The first anionic N-heterocyclic dicarbene, polymeric [:C{[N(2,6-Pr(i)(2)C(6)H(3))](2)CHCLi(THF)}](n) 1, containing both normal (C2) and abnormal carbene (C4) centers in the same five-membered imidazole ring (III), has been prepared by lithiation of the imidazole monocarbene, :C{N(2,6-Pr(i)(2)C(6)H(3))CH}(2). The dicarbene nature of 1 was unambiguously demonstrated by the formation of the group 13 Lewis acid adducts (THF)(2)Li:C{[N(2,6-Pr(i)(2)C(6)H(3))](2)CHC(LA)}, where LA = AlMe(3) [2·(THF)(2)] and BEt(3) [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
196
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(216 citation statements)
references
References 49 publications
(81 reference statements)
15
196
2
3
Order By: Relevance
“…More significantly, aunique broad singlet is observed for the two imidazole CH moieties at d = 4.96 ppm, and is dramatically upfield to that in free IPr (d = 7.20 ppm) and previous C4-metalated examples (range: d = 6.07-6.66 ppm). [12][13]16] This unexpected shielding of the imidazole CH in 2 correlates with the upfield resonances for the para and meta CH groups (at d = 6.43 and 6.86 ppm, respectively) of one of two inequivalent Dipp groups.This effect can be explained by aclose intramolecular spatial proximity between the imidazole CH of one IPr À and aDipp ring from the second IPr À moiety (and vice versa), and results in an overall mutual shielding by anisotropic effects. THF could be af actor in the lack of at emplate effect in the metalation as this lone-pair donor can compete for metal coordination sites and deaggregate the (KNMgN) 6 24 atom ring structure.S ignificantly donor-solvated potassium magnesiate [(PMDETA)KMg(TMP) 2 (CH 2 SiMe 3 )] is known to deprotonate aromatic substrates kinetically through TMP.…”
mentioning
confidence: 65%
“…More significantly, aunique broad singlet is observed for the two imidazole CH moieties at d = 4.96 ppm, and is dramatically upfield to that in free IPr (d = 7.20 ppm) and previous C4-metalated examples (range: d = 6.07-6.66 ppm). [12][13]16] This unexpected shielding of the imidazole CH in 2 correlates with the upfield resonances for the para and meta CH groups (at d = 6.43 and 6.86 ppm, respectively) of one of two inequivalent Dipp groups.This effect can be explained by aclose intramolecular spatial proximity between the imidazole CH of one IPr À and aDipp ring from the second IPr À moiety (and vice versa), and results in an overall mutual shielding by anisotropic effects. THF could be af actor in the lack of at emplate effect in the metalation as this lone-pair donor can compete for metal coordination sites and deaggregate the (KNMgN) 6 24 atom ring structure.S ignificantly donor-solvated potassium magnesiate [(PMDETA)KMg(TMP) 2 (CH 2 SiMe 3 )] is known to deprotonate aromatic substrates kinetically through TMP.…”
mentioning
confidence: 65%
“…Recently, Bertrand et al reported on stable aNHC, [6] and Robinson et al described the lithium complex of a dicarbene with lithium coordination at the second and fourth position of the five-membered imidazole ring. [7] Furthermore, they synthesized the Lewis acid adduct by coordinating two molecules of BH 3 each at the second and fourth position of the five-membered imidazole ring. [8] The NHC·BR 3 (R = H, aryl, alkyl) adduct finds wide-spread [ applications in synthetic chemistry (ionic, organometallic, and radical reactions).…”
Section: Introductionmentioning
confidence: 99%
“…More significantly, a unique broad singlet is observed for the two imidazole CH at 4.96 ppm, dramatically upfield to that in free IPr (7.20 ppm) and previous C4 metalated examples (range: 6.07-6.66 ppm). [12][13]16] This unexpected shielding of the imidazole CH in 2 correlates with the upfield resonances for the para-and meta-CH (at 6.43 and 6.86 ppm, respectively) of one of two inequivalent Dipp groups. This effect can be explained by a close intramolecular spatial proximity between the imidazole CH of one IPr -and a Dipp ring from the second IPr -moiety (and vice versa) which overall results in a mutual shielding by anisotropic effects.…”
mentioning
confidence: 68%